LncRNA HOXA11‐AS drives cisplatin resistance of human LUAD cells via modulating miR‐454‐3p/Stat3. Issue 10 (2nd September 2018) - Zhao, Xia; Li, Xiaoyou; Zhou, Leilei; Ni, Jie; Yan, Wenyue; Ma, Rong; Wu, Jianzhong; Feng, Jifeng; Chen, Ping
Abstract : Over the past several years, long non‐coding RNAs (lncRNAs) have attracted more and more attention due to their special functions. They are vital biomarkers in multiple diseases. LncRNA HOMEOBOX A11 (HOXA11) has been found to be aberrantly expressed in some kinds of malignant tumors. In this study, we mainly discuss the oncogenic role of it in promoting malignant progression and chemoresistance in lung adenocarcinoma (LUAD) cells. The expression of HOXA11‐AS was much stronger in cisplatin‐resistant LUAD cells. Based on The Cancer Genome Atlas database, patients with high expression of HOXA11‐AS had shorter survival time. Additionally, knockdown of HOXA11‐AS caused positive changes in cell activities of LUAD. For example, cell proliferation and migration were weakened, the epithelial mesenchymal transition process was reversed, and apoptosis was induced. These changes were more obvious in cells treated with cisplatin. Next, the HOXA11‐AS/miR‐454‐3p/Stat3 (signal transducer and activator of transcription 3) pathway was found to influence the cisplatin resistance of LUAD cells. HOXA11‐AS specifically acted as a competing endogenous RNA (ceRNA) in LUAD cells. The combinations among these three genes were demonstrated. Finally, rescue assays were applied to demonstrate the ceRNA pattern consisting of HOXA11‐AS, miR‐454‐3p and Stat3. In conclusion, lncRNA HOXA11‐AS acted as a ceRNA to promote cisplatin resistance of human LUAD cells via the miR‐454‐3p/Stat3 axis. Abstract : LncRNA HOXA11‐AS has been studied in several kinds of human malignant tumors, while it was not deeply researched in LUAD. In this study, we uncovered a novel pathway (HOXA11‐AS‐miR‐454‐3p‐Stat3), which was proved to be a functional axis in LUAD. We thought the data were adequate and useful. This study might provide a new therapeutic pathway for LUAD.